Rancang Bangun Alat Simulasi Latihan Menembak Berbasis Arduino Uno - Fiki S. Saro; Sherwin R.U.A. Sompie; Elia K. Allo (Universitas Sam Ratulangi, 2018)
Abstract — This final project aims to create an arduino uno-based arduous training simulation tool that can make it easier to know the score of shots displayed on the smartphone. Shooting scores will be displayed if the photodiode sensor gets or receives light from the laser pointer designed on the weapon, the scores received will be displayed on the seven segment as well as display scores can also be seen on existing applications on the smartphone. the data display on the smartphone has 10 shots data. Of the 10 shots data has been added to a total score that can be viewed on smartphone applications. The data displayed on the smartphone can be sent via bluetooth communication and through the data process from arduino uno to be sent through the bluetooth communication. This shooting simulation tool can make it easier for training and also reduce the budget for shooting practice.Keywords — Arduino, Bluetooth, Photodiode, Shooting, Simulation, Smartphone Abstrak — Tugas akhir ini bertujuan untuk membuat alat simulasi latihan menembak berbasis arduino uno yang dapat mempermudah dalam mengetahui skor tembakan yang ditampilkan pada smartphone. Skor tembakan akan ditampilkan apabila pada sensor photodiode mendapatakan atau menerima cahaya dari laser pointer yang didesain pada senjata, skor yang diterima akan ditampilakan pada seven segment serta tampilan skor juga boleh dilihat pada aplikasi yang ada di smartphone. tampilan data pada smartphone memiliki 10 data tembakan. Dari 10 data tembakan telah dijumlahkan menjadi skor total yang boleh dilihat pada aplikasi smartphone. Data yang ditampilkan pada smartphone dapat dikirim melalui komunikasi bluetooth dan melalui proses data dari arduino uno yang akan dikirim melalui komunikasi bluetooth tersebut. Dengan adanya alat simulasi menembak ini dapat mempermudah untuk pelatihan dan juga memperkecil anggaran untuk latihan menembak.Kata kunci — Arduino, Bluetooth, Menembak, Photodiode, Simulasi, Smartpone